Beyond the Classroom: A Comparative Study of Basic Grammar Instruction in Classroom and Practical Settings for Pre-Departure English Training - Aisyah Nurdianingsih P.A.; Deborah Tirtania Chrisna Pake Seko; Hawa Asma Ul Husna (Jurnal Ilmiah Profesi Pendidikan, 2026)
English proficiency has become an essential competency for vocational students participating in international academic and professional programs. In pre-departure training, English instruction should not only focus on classroom learning but also provide contextual experiences that support real-life communication skills. This study investigates the effectiveness of teaching basic English grammar beyond the traditional classroom through a pre-departure English training program for vocational students at Politeknik Pertanian Negeri Kupang who were preparing for a joint degree program at Jiangsu University. The study aimed to compare the effectiveness of classroom-based instruction and contextual learning in practical settings in improving students’ grammar mastery and speaking ability. Using a quasi-experimental within-subject design, the study involved 14 second-semester students from the Animal Production and Animal Health programs with English proficiency levels ranging from CEFR A1 to B1. The program consisted of 15 meetings, including a pre-test, seven classroom-based grammar sessions, a post-test, six contextual grammar sessions conducted in practical environments such as animal clinics and livestock farms, and a final post-test. Data were collected through grammar tests and speaking assessments administered before instruction, after classroom learning, and after contextual learning. The findings revealed that students showed gradual improvement after classroom instruction and more significant gains after contextual learning, accompanied by higher engagement, confidence, and willingness to communicate. Overall, the study concludes that contextual and experiential learning approaches are more effective in enhancing grammar acquisition and speaking performance among vocational students preparing for international academic mobility.